Transitvity Analysis: Activity Delineation in Short Story “Harry Potter Prequel” by J.K. Rowling - Yessi Ratna Sari (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2022)
It is transitivity that every word has its function and reflect different experience. Transitivity system consists of participant, process, and circumstance. The transitivity system is applied in the short story by J.K Rowling. The purpose of writing this article is to find out the implementation of transitivity system accompanied by functions in each process found in each clause, so that the correct meaning can be obtained. Therefore, this research uses the Functional Grammar theory proposed by Halliday which discusses the function of the clause. The results show that there are 6 types of processes, namely material process, mental process, relational process, behavioral process, verbal process, and existential process, 14 types of participants, namely actor, target, goal, range, carrier, senser, attribute, token, value, phenomenon, behaver, sayer, subject, and existent, and 5 types of circumstances, namely circumstance of time, circumstance of place, circumstance of manner, circumstance of accommodation, and circumstance of cause. Based on the research results, the writer concludes that the author tends to use a material process that emphasizes the many activities carried out by participants. The activities carried out by participants are also supported by other processes. The processes contributed to the creation of a tense atmosphere among the two police officers and the two boys in reaction to the boys’ actions. Other thing that supports the occurrence of these processes is the existence of circumstance.